The British Art Show 1990. - McLellan Galleries, Glasgow; Leeds City Art Gallery; Hayward Gallery, London (London : The South Bank Centre, 1990)
Andrews, Lea ; Bainbridge, Eric ; Flack Audio Film Collective ; Boyce, Sonia ; Bradley, Jyll ; Bright, Kate ; Counsell, Melanie ; Dalziel, Matthew ; Davenport, Ian ; Davey, Grenville ; de Monchaux, Cathy ; Dennis, Jeffrey ; Doherty, Willie ; Hatoum, Mona ; Henderson, Kevin ; Hume, Gary ; etc.
The British Art Show 1990, McLellan Galleries, Glasgow, 24 January - 11 March / Leeds City Art Gallery, 30 March - 20 May / Hayward Gallery, London, 14 June - 12 August
boek